Enhance the rheological properties of reservoir drilling fluid (RDF) using Fe2O3 as nanoparticle material - ALZubaidi, Zaid E. M.; Almahdawi, Faleh H. M.; Mukhtar, Yasir M. F. (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
An effective drilling operation relies substantially on a reliable drilling fluid system, significantly impacting its success. Drilling fluids, particularly reservoir drill-in fluids (RDF), are crucial for minimizing formation damage and maximizing output. As soon as the reservoir is drilled, formation deterioration starts; thus, an optimized RDF with minimal harm is essential considering geology, reservoir fluids, and other factors. This study aims to improve reservoir drilling fluid to minimize skin damage by comparing nanoparticle-based RDFs with conventional drilling fluids used in the Mishrif formation, drilled horizontally 3000 meters. Employing nanoparticles in drilling fluids can improve performance and thermal resistance up to 300°F. Laboratory tests and field data were compared in this study. Nanoparticles in both freshwater and saltwater drilling fluids showed significant enhancements in filtration parameters and rheological qualities. Results indicated that the RDF with Fe2O3 nanoparticles enhanced filtration properties and stability. Optimal Fe2O3 concentrations were 1g at 300°F and 1.5g at 400°F. Adding Fe2O3 nanoparticles to reservoir drilling fluid resulted in a 40% reduction in fluid loss rate and decreased mud cake thickness. Additionally, nanoparticles improved the flow properties of the drilling fluid at high temperatures up to 200°F, ensuring a controlled and more consistent decrease in parameters such as plastic viscosity (PV), yield point (YP), and gel strength without any indication of thermal deterioration.